2012
DOI: 10.1159/000338791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Birth Size and Catch-Up Growth on Adult Blood Pressure and Carotid Intima-Media Thickness

Abstract: Aims: To investigate the effect of birth size and weight gain during childhood on blood pressure and carotid intima-media thickness (cIMT) in young adulthood. Methods: The relationship of birth size with systolic blood pressure (SBP), diastolic blood pressure (DBP), and cIMT was investigated in 243 adults, aged 18–24 years. SBP, DBP, and cIMT were also analyzed in 4 subgroups: subjects either born small for gestational age with short stature (SGA-S) or with catch-up growth (SGA-CU), or born appropriate for ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 74 publications
6
41
0
1
Order By: Relevance
“…Because the current opinions regarding mechanisms for metabolic programming are related to fetal undernutrition and/or rapid catch-up growth with overnutrition, it is relevant to explore the associations stratified according to the degree of prematurity or the degree of growth restriction. 8,35,36 In the present paper, -2015…”
Section: Discussionmentioning
confidence: 78%
“…Because the current opinions regarding mechanisms for metabolic programming are related to fetal undernutrition and/or rapid catch-up growth with overnutrition, it is relevant to explore the associations stratified according to the degree of prematurity or the degree of growth restriction. 8,35,36 In the present paper, -2015…”
Section: Discussionmentioning
confidence: 78%
“…Studies of children born SGA indicate that those who have rapid or disproportionate catch-up in weight are at particularly high risk 119,131,132 . Insulin resistance in young, pre-pubertal, children with SRS can be atypical and difficult to detect in the fasting state; however, impaired glucose tolerance can be confirmed on formal oral glucose tolerance testing 133,134 .…”
Section: Long-term Metabolic Complicationsmentioning
confidence: 99%
“…The majority of individuals with SRS are not routinely followed up, and the small numbers of adults reported have few medical problems. However, it is well recognized that being SGA at birth with accelerated gain in weight for length, particularly during early life, increases the risk of metabolic problems in adulthood 119,132,159 (see previous discussion). Medical problems reported in adult patients with 11p15 LOM include hypertension, dilated cardiomyopathy, type 2 diabetes mellitus, hypercholesterolaemia, fatty liver infiltration, elevated glucose levels and raised HbA 1c levels 135,136,160 ; however, these reports might not be representative of the population as a whole.…”
Section: Adulthoodmentioning
confidence: 99%
“…Previously, Eriksson et al reported that the highest death rates from coronary heart disease occurred in men that were born with LBW or low ponderal index, but whose weight caught up so that they had an average or above average BMI at 11 y of age, suggesting that catch-up growth during childhood modifies the increased risk of death from coronary heart disease in later life (21). Thereafter, many epidemiological studies have demonstrated that infants born preterm or SGA with catch-up growth had a higher risk not only for cardiovascular diseases, but also for developing obesity, hypertension, type 2 diabetes, and MetS in later life (22)(23)(24). Therefore, weight gain during early infancy is a potential target for preventive intervention (25).…”
Section: Catch-up Hypothesismentioning
confidence: 99%